Espacios étnicos y políticos en el área oriental de Iberia. Ethnic and politic spaces in Eastern Iberia - Grau Mira, Ignacio (Complutum, 2005)
The ancient texts referred to pre-roman peoples in the Iberian Peninsula are very ambiguity and vague. For this reasons the possibilities of study these peoples are very scarcety. In this paper we try to approach this topic through the archaeological research related to the ancient Contestani and Edetani that inhabited the modern Valencian Country (Spain). We focus on the links between ethnic identity and state formation in eastern Iberia. In this way, we analysed the archaeological record which allow us define the territorial units and the approach to the societies which created their identity symbols to reinforce the emergence of the states